An intelligent system for personalized conference event recommendation and scheduling - GUNAWAN, Aldy (Institutional Knowledge at Singapore Management University, 2016)
Many conference mobile apps today lack the intelligent feature to automatically generates optimal schedules based on delegates' preferences. This entails two major challenges: (a) identifying preferences of users; and (b) given the preferences, generating a schedule that optimizes his preferences. In this paper, we specifically focus on academic conferences, where users are prompted to input their preferred keywords. Our key contribution is an integrated conference scheduling agent that automatically recognizes user preferences based on keywords, provides a list of recommended talks and optimizes user schedule based on these preferences. To demonstrate the utility of our integrated conference scheduling agent, we first demonstrated the app in the International Conference on Autonomous Agents and Multi-Agent Systems (AAMAS 2015) and conducted a survey to collect some data, which are used to verify the results presented in this paper. It is able to provide well calibrated results with respect to precision, accuracy and recall. We also tested the app in the 2015 WI-IAT International Conference (Singapore). The android and web-based apps have been demonstrated and deployed in AAMAS 2016 (Singapore) with positive responses from the users.